Nano-indentation and indentation size effect on different phases in Lamellar structure high entropy alloy - Nordin, Norhuda Hidayah; Sulaiman, Mohd Hafis; Leong, Zhaoyuan (CRC PRESS, 2021)
In the present work, effects of phase constitution on the tribological properties of FeCoNi(Bx Al1-x)0.1Si0.1 high-entropy alloy (HEA), where x = 0, 0,4, 0.7 and 1.0 are denoted as B0, B0.4, B0.7 and B1.0, respectively, were investigated. The BBC/B2 micro-structure of FeCoNi(Al0.1Si0.1) was changed into a multi-phase system, consisting of FCC and BCC/B2, and Fe2B type intermetallic phases by substitution of boron as shown by X-ray diffraction (XRD). The micro-structures of as-cast alloys were observed to be a lamellar structure comprising nano-structured lamellae with alternating Fe2B and FCC phases. In this work, nano-indentation measurements along with the indents morphologies distinguished the hardness of different phases in the alloy by measuring the effect of the indentation size. Evidences from the results supported that the addition of boron into the single phase HEA with the formation of lamellar structure could provide a balance in strength-ductility in this alloy.